Prognosis of sarcoidosis and factors affecting prognosis - Bilgin, Bilge; Bilgin, Mehmet Kursat; Erol, Serhat; Celik, Gokhan; Ozdemir Kumbasar, Ozlem (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Introduction: Sarcoidosis is a multi-system disease of unknown etiology characterized by non-caseating granulomatous inflammation. Determining the characteristics and prognosis of sarcoidosis cases and revealing the factors that may affect the prognosis are important for approach to patient. This study was planned to obtain prognosis data for our country and to determine the factors affecting the prognosis. Patients and methods: 188 patients, followed regularly for three years or more, admitted to Ankara University Faculty of Medicine, Department of Chest Diseases between 2012-2017 were evaluated retrospectively. Increased radiological findings, functional impairment and any of the clinical conditions requiring initiation/modification of treatment were accepted as progression. Clinical status of the patients at the last follow-up was defined as remission with treatment, spontaneous remission, stable disease, progression, chronic case and recurrence. Spontaneous remission and remission with treatment, regression, stable disease, and recurrence that followed without treatment and didn’t cause symptom or functional impairment were accepted in good prognosis group. Progression, chronic cases that couldn’t be followed without treatment and recurrence requiring treatment were included in poor prognosis group. Results: 58% of patients was accepted in good prognosis and 42% had poor prognosis group. During follow-up, spontaneous remission rate was 20.2%, pulmonary hypertension development rate was 10.6% and mortality rate was 4.25%. Low radiological stage, high spirometry and diffusion capacity values, being asymptomatic and having no previous treatment were associated with spontaneous remission and good prognosis. Increase in serum angiotensin converting enzyme and C-reactive protein and decrease in spirometry parameters and diffusion capacity values were associated with progression.